Service Quality and Customer Satisfaction: Evidence From State Commercial Banks in Ampara District - A.L. Abdul Rahuman; A.R. Mohamed Akram; M.Siraji (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The banking industry plays a crucial role in the industry and economic growth of a country. The products and services offered by banks are significant to attain a competitive edge. The research study empirically finds the effects of service quality dimensions in improving the customer satisfaction of state commercial banks in the Ampara district quantitatively by using a deductive approach. The present study focuses on the factors determining service quality and customer satisfaction. Data was collected from 275 customers from the Ampara district. The conceptual model was formed and categorized under human-related factors, non- human-related factors. Accordingly, hypotheses were formed to examine the relationship that exists between service quality and customer satisfaction. The research study empirically found that there is a positive relationship exist between service quality and customer satisfaction while human-related factors have a great impact on customer satisfaction than non- human-related factors. Reliability and Assurance are the most influential determinants of customer satisfaction in-state commercial banking industry. The findings and managerial implications were suggested to state commercial banks to invest more efforts towards human-related factors than non-human related factors to uplift their service quality to attract and retain their valuable customers.